2005
DOI: 10.1242/dev.01790
|View full text |Cite
|
Sign up to set email alerts
|

The CARD-carrying caspase Dronc is essential for most, but not all,developmental cell death inDrosophila

Abstract: The initiator caspase Dronc is the only Drosophila caspase that contains a caspase activation and recruitment domain (CARD). Although Dronc has been implicated as an important effector of apoptosis, the genetic function of dronc in normal development is unclear because dronc mutants have not been available. In an EMS mutagenesis screen,we isolated four point mutations in dronc that recessively suppress the eye ablation phenotype caused by eye-specific overexpression of hid. Homozygous mutant dronc animals die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
244
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(271 citation statements)
references
References 74 publications
20
244
2
2
Order By: Relevance
“…Genetic inactivation of dronc blocks most developmental cell death during embryogenesis, imaginal disc development and metamorphosis. [8][9][10][11] Dronc is functionally similar to human Caspase-9 because it contains a CARD motif in the prodomain, 12 and interacts with Drosophila Apaf-1-related killer (Ark), also known as Dark, Hac-1 and D-Apaf-1 (reviewed in Ref. 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic inactivation of dronc blocks most developmental cell death during embryogenesis, imaginal disc development and metamorphosis. [8][9][10][11] Dronc is functionally similar to human Caspase-9 because it contains a CARD motif in the prodomain, 12 and interacts with Drosophila Apaf-1-related killer (Ark), also known as Dark, Hac-1 and D-Apaf-1 (reviewed in Ref. 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to upstream death stimuli, the initiator caspase Dronc is auto-activated as a component of the apoptosome, and further activates effector caspases, including DrICE and DCP-1. 34 In this experiment, we knocked down ubr3 in a Dronc mutant background and found that the cell death induced by ubr3 RNAi was massively suppressed in the absence of Dronc (Figures 4e and f). This result argues that Ubr3 acts upstream of Dronc in the apoptosis pathway.…”
Section: Ubr3 Regulates Apoptosis Q Huang Et Almentioning
confidence: 89%
“…Dronc I29 is described previously. 34 H99 is a deletion of hid, rpr and grim. A null allele of ubr3 1 was generated by P-element-mediated imprecise excision from p (EP) EP1243, which deletes 1555 bp including the start codon and the first exon.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] In fact, mutants of diap1, dronc and drICE genes were isolated in genetic screens searching for modifiers of the eye ablation phenotypes caused by reaper or hid overexpression. [21][22][23][24][25][26][27] Mammalian IAP antagonists are Smac/Diablo and HtrA2/Omi, which function similarly to the RHG proteins. 28 Abbreviations: ALPS, autoimmune lymphoproliferative syndrome; APF, after puparium formation; Ced-3, cell death defective 3; CyO, curly of Oster; Dcp-1, death caspase 1; DIAP1, death-associated inhibitor of apoptosis 1; DNA, desoxyribonucleic acid; drICE, death-related ICE (interleukin converting enzyme); dronc, death regulator Nedd2-like caspase; EMS, ethyl methanesulfonate; Ey, eyeless; Flp, flippase; FRT82B, flippase recombination target at 82B; GFP, green fluorescent protein; Gh, GMR-hid; Hid, head involution defective; GMR, glass multimer reporter; HtrA2, high-temperature-required protein A2; IAP, inhibitor of apoptosis protein; PCR, polymerase chain reaction; R8, photoreceptor 8; RHG, reaper, hid, grim; Smac/Diablo, second mitochondria-derived activator of caspases/direct IAP binding protein with low pI; TUNEL, terminal deoxynucleotidyl transferase dUTP nick end labeling; Ubi, ubiquitous; wt, wild-type; XIAP, X-linked inhibitor of apoptosis…”
mentioning
confidence: 99%
“…[12][13][14] In fact, mutants of diap1, dronc and drICE genes were isolated in genetic screens searching for modifiers of the eye ablation phenotypes caused by reaper or hid overexpression. [21][22][23][24][25][26][27] Mammalian IAP antagonists are Smac/Diablo and HtrA2/Omi, which function similarly to the RHG proteins. [28][29][30][31] Both IAPs and IAP antagonists are under tight control by various mechanisms to ensure proper regulation of caspase activity.…”
mentioning
confidence: 99%